A Retrospective Analysis of the Factors Affecting the Detection of T790M-resistant Mutation on Rebiopsies for Patients with Non-small-cell Lung Cancer Harboring EGFR Mutations - Mouri, Atsuto; Miura, Yu; Hashimoto, Kousuke; Shiono, Ayako; Kobayashi, Kunihiko; Uchida, Takahiro; Kaira, Kyouichi; Nishihara, Fuyumi; Yamaguchi, Ou; Kagamu, Hiroshi (The Journal of the Japan Society for Respiratory Endoscopy, 2020)
Background/Objective. Osimertinib is generally used as a second-line or later therapy after the detection of a T790M mutation by a rebiopsy in non-small-cell lung cancer (NSCLC). However, few reports have described the results of rebiopsies in NSCLC patients with EGFR mutations. The aim of our retrospective study was to identify factors affecting the detection of a T790M mutation in patients who undergo a rebiopsy. Method. This study included subjects who had advanced NSCLC with EGFR mutations and underwent rebiopsies at our hospital from January 2016 to April 2018. We investigated the success rate of rebiopsies, the detection rate of T790M, and the influential factors related to rebiopsies and T790M detection. Result. The subjects were 58 patients who underwent a rebiopsy. The success rate of the first rebiopsy was 74.1% (43/58), and the T790M-positive rate was 41.9% (18/43). The success rate of the second rebiopsy was 78.6% (11/14), and the T790M-positive rate was 63.6% (7/11). The overall number of rebiopsies was 75, the overall success rate of rebiopsies was 76.0% (57/75), and the overall T790M-positive rate was 43.9% (25/57). No statistically significant factors affecting the T790M-positive rate were observed in this study. In addition, the characteristics of patients who underwent multiple rebiopsies as well as the characteristics of those who only underwent a single rebiopsy were examined. The frequency of experiencing multiple rebiopsies was higher in patients with cytotoxic agents than in those without (P=0.005). Conclusion. We were unable to detect any factors affecting positivity for a T790M mutation. The frequency of having undergone several rebiopsies seemed to be higher in patients who received any cytotoxic chemotherapy than in those with no such treatment. We believe that repeated specimen collection may increase the detection rate for T790M mutations.